Teachers and football : schoolboy association football in England, 1885-1915 - Kerrigan, Colm (Woburn education series., 2005)
This is a fascinating account of the origins of schoolboy football and the factors that have influenced its development and the consequences and benefits that have followed not only for school football but for sport in schools and communities as a.